Is the Level of Financial Sector Development a Key Determinant of Private Investment in the Power Sector? - Ba, Lika; Gasmi, Farid; Noumba Um, Paul (2012)
This paper seeks to assess the extent to which a country's overall level of development and that of its financial sector, in particular, are factors that attract private capital into infrastructure projects. The authors investigate these effects in a 1990-2007 dataset on the power sector in 37 developing countries. The results suggest that economic growth is a key determinant of private investors' investment in infrastructure projects, and that investors tend to take countries governance quality into account in their decisions to invest. The empirical results highlight that the development of the financial sector also plays a significant role in private investors' decisions to enter infrastructure sectors. In particular, the degree of country risk and exchange rate volatility is found to be negatively related to the volume of private sector investment in power projects. Furthermore, when the banking sector and the capital market are separately treated in the analysis, the existence of a well functioning capital market is the main attracting factor. In addition, the existence of an independent energy regulatory authority significantly improves the level of private investors' implication in energy projects. When accounting for the interactions between the overall economic development and the financial sector development variables, the effects of these variables are still significant and the results also confirm the importance of an independent energy sector regulator.